ENT 530 Social Media Portfolio: Sambal Hitam Tokthevaini / Rosmalinda Mohd Nusi - Mohd Nusi, Rosmalinda (2021)
Sambal Hitam Tokthevaini or locally known as Sambal Hitam Pahang is the traditional delicacies of Pahang. The product has gone through evolution in terms of packaging and delivery of product presentation. Previously we may get this product only on certain occasions back in the village. The use of method will tell the story how difficult the process of making the sambal and uniqueness of its ingredients is. Sambal Hitam most likely came about when there is an abundance of Belimbing buluh. This recipe was created to utilize these fruits rather than have it put to waste. This sambal is specifically well known in a few regions in the state of Pahang, namely Temerloh, Jerantut, Raub & Kuala Lipis. The name is reflected by the colour of the Belimbing after being boiled for a length of time. This is a favourite sambal of mine due to its sourness, spiciness and the crunchiness of the anchovies. I created a Facebook page to promote my business through social media which I have posted soft sell and hard sell promotion to let people know about my products. I also promote this Sambal Hitam Pahang in Whatsapp through personal messages and groups.